EXPLORING THE RELATIONSHIPS BETWEEN PSYCHOLOGICAL CHANGES, SLEEP QUALITY, AND HYPERTENSION AMONG COMMUNITY-DWELLING ELDERLY - Dhea Natashia; Pricelia Alifa Rahma; Dian Fitria; Syamikar Baridwan Syamsir; Diana Irawati (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2024)
Objective: to examine the relationship between psychological changes and sleep quality with the incidence of hypertension in the elderly.Method: This cross-sectional study, conducted with a purposive sample of 126 elderly participants, assessed psychological changes using the Depression, Anxiety, and Stress Scale (DASS-42) questionnaire and sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Blood pressure was measured using a sphygmomanometer to assess hypertension. Data analysis included independent t-tests and chi-square tests, with logistic regression used to identify predictors of hypertension. Results: The independent t-test revealed significant differences in stress levels between participants with and without hypertension (t = -6.614, p = 0.020). Similarly, significant differences in depression levels were observed between these two groups (t = -0.044, p = 0.014). Elderly individuals with poor sleep quality had a 5 times higher risk of experiencing hypertension (OR = 4.625, p = 0.008). Multivariate analysis indicated that age was a predictor of hypertension incidence (β = 0.208, p = 0.004), and sleep quality was also a predictor (β = -1.501, p = 0.023). Discussion: The findings suggest that psychological factors and sleep quality influence hypertension development in the elderly, likely through physiological mechanisms such as heightened sympathetic activity and vascular stress. These results highlight the importance of addressing both psychological health and sleep quality in managing hypertension risk. Conclusion: Sleep quality is a predictor of hypertension incidence in the elderly. Those with poor sleep quality have a 5 times greater risk of developing hypertension compared to those with good sleep quality. Keywords: elderly, hypertension, psychological changes, sleep quality